Introduced North American Black Henbane (Hyoscyamus niger) Populations are Biennial. (December 2014) - Fettig, Christa E.; Hufbauer, Ruth A.
Abstract: Black henbane can be either annual or biennial. We investigated which life cycle is found in four introduced western North American populations. Plants were grown in a greenhouse common garden until half were vernalized by exposure to natural winter temperatures, while the other half remained in the greenhouse above 20 C, with 16 h of light and 8 h of dark. In total the plants were monitored 313 d after germination. We measured whether plants bolted, the time it took for bolting to commence, and the size at bolting. All vernalized plants bolted after 117 d of active growth (within 26 d of the end of the vernalization treatment), whereas only 26% of the nonvernalized plants bolted after an average of 278 d of active growth. Vernalized plants bolted at a smaller size than the nonvernalized plants that bolted (28 vs. 41 leaves on average). In the nonvernalized plants, the relationship between time to bolting and size was strong, but not so with the vernalized plants. Our results indicate that introduced black henbane plants are biennial, and that vernalization is more critical to bolting and flowering than reaching a certain size. Nonetheless, the fact that nonvernalized plants were capable of bolting if grown long enough suggests that vernalization is not the only cue that can trigger reproduction in introduced populations.